(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Personality reflects adaptive human behavior adaptability to changing situations as well inevitably affects living a happy life Both in terms of physical and mental health. To study the level of 5 dimensions of personality and adaptive behavior. after the coronavirus epidemic, as well as to study the ability to explain 5D personality variation and adaptive behavior after the coronavirus epidemic of high school students Samut Songkhram Province. This research is an explanatory research using a cross-sectional survey. The sample is high school student Samut Songkhram Province, 347 people used a questionnaire to collect data. Data were analyzed by descriptive statistics including number, percentage, mean and standard deviation and analyzing the ability to explain 5-dimensional personality variation and adaptive behavior after the epidemic of the coronavirus with Multiple Regression Analysis, setting a statistical significance level of 0.05. Most of the students had a personality type. Consciousness had the highest average, students had the highest average family adaptive behavior, and sensitive personality and openness to new experiences. Be able to explain the variation in adaptive behavior after the situation Coronavirus epidemic 36.00% promoting personality for students to have the ability to adapt to appropriate situations Affecting the quality of life of students in various aspects of life, school administrators should have a policy and regularly monitor the situations of students’ adaptive behavior in a concrete way to reduce physical and mental problems and ensure students have an appropriate quality of life.